(3CNHGQ CHj GdfhGSs - (3CHh gaGf YHO Gddg Hf CMeO Hf MQH GdegPej, CHhgaGf,J (B257 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI (B: (3CNHGQ CHj fhGS LeY CHj gjaGf YHO Gddg Hf CMeO Hf MQH QMegeG Gddg s
(3BNQgG (B:s
(3jfJgi HbUjOI fgGjJgG (B: (3hGf eMeOkG Y HOkG QShdG Edi GdKbdjf GQSdg Gdedjc aGfXQ jG CNj Edi gPg GdGHjGJ YfO GdNGJeI s
(3CNP Yf GdCUeYi hQhi Yfg jehJ Hf GdeRQYs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B6 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs